The Relationship and Gender Disparity Between Thyroid Nodules and Metabolic Syndrome Components Based on a Recent Nationwide Cross-Sectional Study and Meta-Analysis - Zhang, Fan; Li, Yongze; Yu, Xiaohui; Wang, Xichang; Lin, Zheyu; Song, Bo; Tian, Lijun; Feng, Chuyao; Shan, Zhongyan; Teng, Weiping (Frontiers in Endocrinology, 2021)
Background: Metabolic syndrome (MetS) has a potential connection with thyroid disease, but its relationship with thyroid nodules (TNs) is still controversial. This study aims to clarify the relationship between MetS and TNs, and this relationship in the subgroup of gender. Methods: The recent nationwide cross-sectional study called Thyroid Disorders, Iodine Status, and Diabetes Epidemiological survey provided the newest data on the relationship between MetS and TNs from China and included 56,729 subjects. We also researched related literature in PubMed, EMBASE, Cochrane Library, and MEDLINE until Oct 30, 2020, in order to perform a meta-analysis. The relevant articles were examined, and the eligible studies were included to assess the association between MetS and TNs. Results: The meta-analysis included 15 studies (involving 468,845 subjects). Of these, 14 studies were from the databases, and one study was this cross-sectional data. The meta-analysis showed that TNs were associated with a higher prevalence of MetS (OR=1.87, 95% CI: 1.44–2.45) and the components of MetS, including central obesity (OR=1.41, 95% CI: 1.15–1.72), hypertriglyceridemia (OR=1.13, 95% CI: 1.10–1.15), low high-density lipoprotein cholesterolemia (OR=1.11, 95% CI: 1.02–1.20), abnormal blood pressure (OR=1.68, 95% CI: 1.62–1.75), and hyperglycemia (OR=1.59, 95% CI: 1.46–1.74). Central obesity displayed gender differences, being a risk factor in males (OR=1.38, 95% CI: 1.02–1.86) but not in females (OR=1.47, 95% CI: 0.97–2.23). Conclusion: TNs were indeed associated with a higher prevalence of MetS. In addition, its component diseases, such as central obesity, hypertriglyceridemia, abnormal blood pressure, and hyperglycemia, were also associated with TNs. Females with MetS or its components had a higher risk of suffering from TNs than males.